Labour force by sex (Ministry of Finance and Planning. Central StatisticalOffice Port of SpainTT, 1985)
Provides estimates of labour force for the period July to December 1984. Statistics describe the labour force by employment status, sex, age, industrial group, occupational group, and type of worker. Includes statistics for earlier periods.
IDS